2017
DOI: 10.2147/ijn.s124965
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of in vivo degradability, vascularization and osteogenesis of calcium sulfate-based bone cements containing nanoporous lithium doping magnesium silicate

Abstract: Nanoporous lithium doping magnesium silicate (nl-MS) was introduced into calcium sulfate hemihydrate to prepare calcium sulfate composite (nl-MSC) bone cements. The introduction of nl-MS improved the in vitro degradability of nl-MSC cements, which could neutralize acidic degradable products of calcium sulfate and prevented the pH from dropping. The cements were implanted into the bone defects of femur bone of rabbits, and the results of histological and immunohistochemical analysis revealed that massive new bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…16−18 It indicates that calcium sulfate has good properties of promoting bone healing. 19 In other words, calcium sulfate can be used as a carrier for proangiogenic drugs. However, it has been proved that pure calcium sulfate materials degrade so faster than bone regeneration that it may lead to the formation of voids in the bone defect area and hinder osteogenesis after full degradation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16−18 It indicates that calcium sulfate has good properties of promoting bone healing. 19 In other words, calcium sulfate can be used as a carrier for proangiogenic drugs. However, it has been proved that pure calcium sulfate materials degrade so faster than bone regeneration that it may lead to the formation of voids in the bone defect area and hinder osteogenesis after full degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium sulfate has been widely used as a host material to design resorbable orthopedic implanted materials due to its biodegradability, biocompatibility, and osteoconductivity . Besides, calcium sulfate, because of its good self-curing properties, has been proved that it could be used as a desirable drug carrier for local spatial and temporal sustained release in previous studies. It indicates that calcium sulfate has good properties of promoting bone healing . In other words, calcium sulfate can be used as a carrier for proangiogenic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that lithium can promote osteogenic differentiation of BMSCs by activating the Wnt/GSK-3 signaling pathway 15 , 16 . In vivo studies demonstrated that lithium has promoting effect on bone regeneration and can improve osteoporosis 17 , 18 . In recent studies, lithium salts have been introduced into bone tissue engineering and have been shown to play an important role in improving the osteogenesis of biomaterials 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%
“…A nanoporous structure on biomaterials can promote cell adhesion, proliferation, differentiation, and osteogenesis-related gene expressions, while macroporous structures accelerate osteogenesis and improve mechanical interlocking of ingrowth of NBs, providing greater mechanical stability at the critical interface and hence promoting ossteointegration 21. Nanoporous magnesium silicate (nMS) is a bioactive glass that possesses a nanoporous structure with large surface area and high pore volume 18. Our previous research has confirmed that the nMS exhibits superior in vitro bioactivity, cytocompatibility, and in vivo osteogenesis 19…”
Section: Introductionmentioning
confidence: 99%